A conative educational model for an intervention program in obese youth - Vanhelst Jérémy; Béghin Laurent; Fardy Paul; Bui-Xuan Gilles; Mikulovic Jacques (BMC, 2012)
Abstract Background Obesity in children has increased in recent years throughout the world and is associated with adverse health consequences. Early interventions, including appropriate pedagogy strategies, are important for a successful intervention program. The aim of this study was to assess changes in body mass index, the ability to perform sport activities, behavior in the classroom and academic performance following one year of a health-wellness intervention program in obese youth. Methods The CEMHaVi program included 37 obese children (19 girls and 18 boys). Participants received an intervention program consisting of physical activity and health education. Assessment included body mass index, academic performance, classroom performance and ability to perform sport activities. Paired t tests were used to assess the effects of intervention, and chi square was used to assess inter-action between measures. Results Findings of the study suggest significant decrease in Z scores of Body Mass Index and an improvement of academic performance, classroom behavior and the ability to perform sport activities (p < 0.05). Chi square testing showed significant positive inter-actions between body mass index, classroom behavior and academic performance. Conclusions Results following year one of CEMHaVi showed that a program of physical activity and health education had positive effects on obesity, behavior in the classroom and the ability to perform sport activities in obese adolescents. Significant inter-action in changes between variables was observed. Findings are important for designing intervention models to improve health in obese youth.